PETA KEMAMPUAN KEUANGAN DAERAH PADA PEMERINTAHAN KOTA DAN KABUPATEN SE-JAWA DAN BALI TAHUN 2004-2008: METODE KUADRAN - Samora, Remon (Jurnal Akuntansi Kontemporer, 2010)
Regional autonomy is aimed at bringing the region's independence in financing the region's expenditures. In its implementation, regional autonomy is still not able to realize the regions independence because each region has different characteristics so that it's required a different policy. This study aims to map the regions finance by independent and potential regions, independent and less potential regions, non-independent and potential regions, and nonindependent and less potential regions. Independent variables used are the growth ratio and the share ratio which is calculated using the District Revenue (PAD), Tax Sharing (BHP), Non-Tax Sharing (BHBP) and Total Expenditure